2020
DOI: 10.3389/fpsyg.2020.00544
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linguistic Word Recognition Development Among Chinese Children: A Multilevel Linear Mixed-Effects Modeling Approach

Abstract: The effects of psycholinguistic variables on reading development are critical to the evaluation of theories about the reading system. Although we know that the development of reading depends on both individual differences (endogenous) and itemlevel effects (exogenous), developmental research has focused mostly on average-level performance, ignoring individual differences. We investigated how the development of word recognition in Chinese children in both Chinese and English is affected by (a) item-level, exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In addition, the linguistic features and the learners’ characteristics should be considered jointly as suggested by previous studies on word recognition in both Chinese and English ( Guan and Fraundorf, 2020a ; Guan et al, 2020b ). Our findings support Guan et al (2020b) , who through longitudinal comparison showed that word-recognition abilities are script-specific at first.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the linguistic features and the learners’ characteristics should be considered jointly as suggested by previous studies on word recognition in both Chinese and English ( Guan and Fraundorf, 2020a ; Guan et al, 2020b ). Our findings support Guan et al (2020b) , who through longitudinal comparison showed that word-recognition abilities are script-specific at first.…”
Section: Discussionmentioning
confidence: 99%
“…That is, early script effects are influenced by an item-by-subject interaction in each language, with item-level features of the newly learned language interacting with characteristics of individual participants. Previous studies have shown that the consistency of words, orthographic awareness, morphological awareness, and linguistic abilities interact ( Guan and Fraundorf, 2020a ). In addition, effects at the item level generally decrease with age, as individual differences in participants’ linguistic awareness (e.g., orthographic awareness and morphological awareness) contribute more to successful performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past two decades, many cross-disciplinary scholars have attempted to solve these problems. These studies mainly focused on character recognition (e.g., Siok and Fletcher, 2001 ; Liao et al, 2008 ; Guan and Fraundorf, 2020 ; Jiang et al, 2020 ; Zhang H. et al, 2020 ; Zimmer and Fischer, 2020 ; Guan et al, 2021 ), without considering the role of the embodiment of handwriting, which is deemed essential to the embodied cognition theory (ECT). Specifically, the ECT underlines the interaction among perception, action, body, and the environment ( Barsalou, 2008 ).…”
Section: Introductionmentioning
confidence: 99%